The Utilization of Aquatic Weeds as Biomonitoring Agent for Trophic Status of Water Reservoir Ecosystem - Dwi Nugroho Wibowo; Agatha Sih Piranti (Jurnal Agrista, 2007)
ABSTRACT. An ecological study of aquatic weed for biomonitoring trophic status of water reservoir system was conducted in Rawa Pening Water Reservoir, Ambarawa, Semarang Regency. This research was conducted from February to October 2006. Variables of study were taken from nine selected observation stations representing upstream, middle, and downstream both in wet season and dry season. The study was aimed to investigate the diversity of aquatic weed in Rawa Pening Water Reservoir at the three zones in both season in order to obtain bioindicator for trophic status of water reservoir ecosystem. The analysis on community structure of aquatic weed was carried out by describing data on the diversity of aquatic weed species. The similarity of aquatic weed characteristics among zones was analyzed on the basis of average similarity dendogram. The variation of water quality and aquatic weed characteristics among stations was analyzed using multivariate analysis based on the analysis of main component, while spatial distribution of aquatic weed was analyzed using correspondence factorial analysis. Based on the variation of characteristics of water quality, Rawa Pening Water Reservoir belongs to eutrophic status. Low diversity of aquatic weed in Rawa Pening Water Reservoir both in wet season and dry season (12 species) was observed. The dominant species in both season were Eichhornia crassipes and Salvinia natans. Other species found were Hydrilla verticillata, Pistia stratiotes, Chara sp., Nitella sp., Ipomoea aquatic, Cyperus cephalotes, C. pilosus, Alternanthera philoxeroides, Nymphoides indica, and Sacciolepis interrupta. Both in wet season and dry season, spatial distribution on the basis of aquatic macrophyte weed was evenly distributed and had grouping pattern of sufficienly high similarity ( 70%). The group tended to be dominated by E. crassipes and S. natans.